(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
A description is given of apparatu’s for isdation vo1atile oils form various parts of plants. The detennination of volatiie oil in the as Ticultura! products were made by distilling the materials with water, collecting the distillate in a graduated tube in which the aqueous portion of the distillate is uatomatically separted and returned to the distilling flask) and measuring the volurne of the oil. the averaqe percetage of volatile oil content ’as calculated on dried plant material by volum.a(v). the concentrate was then examined by gas liquid chromatogaphy. Volatile oils are the odorus principles found in various plant parts. Because they evaporate when exoosed to the air at ordinary tem. pefati.lr8i ti’.ey called voiatile oils! ethereal oils or essential oils. volatile oils consists of mixtures of chemical 11hich are often quite cOlllplex and ’TaI’y widely in chemical compoition (1 ) 2) 3J 4). Several meti-rods were used for isolation or extraction the volatile o11s from the plant. materials. Distillation was tbe most common m.ethod used by industrial firms: Three types of distilation were used (1) ’l)latir distillation is applied to the dried plant ulatsrial and not subjected to injUl’Y by boiling . (2) vater and stem distillation is employed for Subsuillces eitiler dried or fresh that may rnay be injured by boiling. (3) direct steam distillation applicable to fresh plant materials (5)6)4). In the perfume industry the solvent extraction method was used for extraction of the volatile Oils by using organic solvent such as petroletUll etiler or benzen. however) becaus of the high cost involved the extraction process probably will not be adopted by firftl,S producing \1r)latila oil. establisged distillation r.r..ethod is a 10v cost operation compared to the extraction process (7) 8). Identification of the volatile constituents were carried out by gas liquid chromatography (9)0) The present paper givas a detailed description of apparatus which were sutable for isola.tion the lighter and tile heavier u.(’-m water volatile oils fronl differenet plant materials. Meanwhile tbe purity of tile concentrates were ex lrined by g-aS liquid chromato graphy( GLe).